THE FREQUENCY OF VSR (VENTRICULAR SEPTAL RUPTURE) AFTER ACUTE STEMI ST-ELEVATION MYOCARDIAL INFARCTION IN TERTIARY CARE HOSPITAL - RAHIM , A; ALI , J; SAJJAD , W; BILAL , A; REHMAN , SU; JAN , DA; ULLAH , R (Biological and Clinical Sciences Research Journal, 2023)
The purpose of the study was to find out how frequently ventricular septal rupture occurred in patients who had an acute ST-elevation myocardial infarction and then visited the cardiology department of Lady Reading Hospital in Peshawar. The cross-sectional design was employed in the investigation, which took place between April 6, 2018, and April 12, 2018. A thorough history and standard physical examination were performed on 346 patients while under observation. Baseline tests such as transthoracic echocardiography and electrocardiography were carried out to evaluate ventricular septal rupture. Records included age, gender, type of STEMI, diabetes mellitus, smoking, history of CAD, and prodromal angina. The study’s findings indicated that the patients’ mean age was 53, with a standard deviation of ±11.23. Of the patients, 32% were female and 68% were male. Furthermore, ventricular septal rupture was present in 5% of the patients but not 95%. Thus, the study concludes that 5% of cases of ventricular septal rupture followed an acute ST-elevation myocardial infarction.